Framing and Themes of the City of Boulder's Sugar-Sweetened Beverage Tax Coverage in the Local News From 2016 to 2018 - Kristen Daly, PhD, MPH; Meredith Fort, PhD, MPH; Jennifer Falbe, ScD, MPH (Elsevier, 2023)
The objective of this paper was to analyze the contents of opinion and news articles related to the city of Boulder's sugar-sweetened beverage excise tax campaigns in Boulder's only local newspaper. We searched for articles in The Daily Camera related to the sugar-sweetened beverage tax, published from January 2016 to December 2018. We conducted a content analysis, categorizing 152 relevant articles by type, authors, and frames (pro, anti, neutral) on the basis of the preponderance of arguments, themes, and use of evidence. The majority of articles were opinion (n=92) versus news (n=60). Most articles were pro-frame (n=78) versus anti-frame (n=37) and neutral frame (n=37). Pro-frame articles were more likely to cite evidence in support of arguments or the professional credentials/experience of the authors. The most frequent pro-frame themes were health, benefits of the revenues, equity, and unethical tactics of the industry. The most frequent anti-frame themes were economic consequences, claims that the measure was confusing, government overreach, and purported ineffectiveness of taxes. The leveraging of local issues by the beverage industry was observed. Themes identified in the news regarding Boulder's successful sugar-sweetened beverage tax may appear in future sugar-sweetened beverage policy campaigns and should be anticipated.